Medical drainage of pancreatic pseudocsysts [1] - Cihangiroglu, M. (My University, 1999)
[Abstract Not Available]
Pankreas psodokistlerinin medikal drenaji
Keywords: echography; letter; pancreas pseudocyst; percutaneous drainage; peritoneal catheter; tomography